Indirect measurement of sinoatrial conduction time in patients with sinoatrial disease and in controls. Issue 7 (July 1977) - Crook, B; Kitson, D; McComish, M; Jewitt, D
Abstract : Clinical recognition of sinoatrial disease currently depends on the presence of transient sinus bradycardia, sinoatrial block, or supraventricular tachyarrhythmias. The value of clinical electrophysiological assessment in these patients is not clear. Using intracardiac electrophysiological recordings and programmed stimulation we have examined 14 patients with sinoatrial disease and 11 control patients undergoing investigation for chest pain. Intracardiac conduction times were normal in all patients. There was no significant difference of sinus node recovery times between the sinoatrial disease and control groups. Sinoatrial conduction times were measured by the indirect method and two populations were identified. However, the mean values of 128 +/- 27 ms in patients and 112 +/- 30 ms in controls were not significantly different and major overlap rendered this measurement clinically valueless. It is concluded that no current electrophysiological measurement has diagnostic value in patients with sinoatrial disease.